Adsorption Isotherm of Some Heavy Metals in Water on Unripe and Ripe Peel of Banana - Sirilert, Mintra; Maikrang, Kamol (Naresuan University Journal: Science and Technology (NUJST); Vol 26 No 1 (2018): January - March 2018, 2018)
The use of banana peels for removing heavy metals from water was a promising alternative due to the fact that they are abundantly available as agriculture wastes and are available at a low price. In the present study, the potentiality of unripe and ripe banana peels as adsorbents for removing cadmium and lead ions from aqueous solution was investigated by adsorption. The effect of pH, adsorbent dosage, contact time and initial metal concentration were investigated. The experimental result showed that adsorption of cadmium on ripe and unripe banana peels increased with the increase in pH. Maximum uptake took place at pH 3.0 and 5.0 using ripe and unripe banana peels as adsorbent, respectively. The optimum dosage was selected as 30 g/L and the contact time was achieved at 20 minutes for both types of banana peels. For lead adsorption, the maximum adsorption occurred at pH 4.0 and 5.0 with an adsorbent concentration of 40 g/L at 20 minutes using ripe and unripe banana peels as adsorbent. The adsorption phenomenon was fitted with Langmuir isotherm indicated monolayer adsorption. Cadmium uptake capacity was 1.9051 and 2.6185 mg/g using unripe and ripe banana peels, respectively. For lead, the maximum adsorption capacity was 1.630 and 2.8810 mg/g using unripe and ripe banana peels, respectively. Hence, ripe banana peels have greater potential than unripe banana peels for both types of metal ions adsorption. The removal of lead had a higher adsorption capacity than cadmium.
Keywords: Science technology